ECOLOGICAL REALITY: Its Crisis and Praxis - Inchody, Oliver (Journal of Dharma, 2011)
The ecological reality that shapes the consciousness of a human mind has a dual face: the crisis it undergoes and its praxis. This presentation delineates the dual face of the ecological reality, crisis and praxis, as a basis for an ecological conscientisation appropriate to an average human mind.